DEVELOPMENT OF EGGS FROM FASCIOLA HEPATICA EGGS ISOLATED OF GALLBLADDER OF SHEEP AND CATTLE, EXPOSED TO LIGHT AND DARKNESS - Iturbe Espinoza, Paul (2011)
The development of eggs to obtain ciliated larvae called miracidia of Fasciola hepatica in the nature occur in aqueous biotopes or shallow banks of accumulations of water where the eggs come in fecal waste. The objective of this research was to make the hatching of miracidia exposed to light and darkness from eggs of F. hepatica from gall bladders of cattle and sheep hosts, and whether there are significant differences in the time of their evolution. The samples from 5 cattle and 10 sheep were collected from July to September 2009. Sieved and washed in cooled boiled water, placing 20 cm3 of sediment in each petri dish in triplicate and a constant temperature of 26°C and were observed daily until hatching, adding cooled boiled water to compensate the evaporation. Developing longer corresponded to the eggs incubated in darkness, being of 404 h and 439 h on eggs of origin sheep and cattle, respectively. The development period was shorter for eggs incubated in the presence of light. Provenance in sheep and cattle was 278 h and 279 h, respectively. Light and origin of the host influence hatching time of eggs of F. hepatica.